Resistivity and induced polarization : theory and applications to the near-surface earth - Binley, Andrew, 1961-; Slater, Lee, 1969- (Cambridge : Cambridge University Press, 2020)
Resistivity and induced polarization methods are used for a wide range of near-surface applications, including hydrogeology, civil engineering and archaeology, as well as emerging applications in the agricultural and plant sciences. This comprehensive reference text covers both theory and practice of resistivity and induced polarization methods, demonstrating how to measure, model and interpret data in both the laboratory and the field. Marking the 100 year anniversary of the seminal work of Conrad Schlumberger (1920), the book covers historical development of electrical geophysics, electrical properties of geological materials, instrumentation, acquisition and modelling, and includes case studies that capture applications to societally relevant problems. The book is also supported by a full suite of forward and inverse modelling tools, allowing the reader to apply the techniques to a wide range of applications using digital datasets provided online. This is a valuable reference for graduate students, researchers and practitioners interested in near-surface geophysics.
Title from publisher's bibliographic system (viewed on 18 Dec 2020).
Keywords: Earth resistance (Geophysics); Induced polarization; Geophysics -- Technique; Geophysics -- Methodology; Geophysics -- Data processing